New-onset diabetes mellitus after living-donor liver transplantation: association with graft synthetic function - Yagi, Shintaro; Kaido, Toshimi; Iida, Taku; Yoshizawa, Atsushi; Okajima, Hideaki; Uemoto, Shinji (Surgery today (Tokyo, Japan), 2017)
Background and purpose It is now known that post-transplant graft function after deceased-donor liver transplantation and living-donor liver transplantation (LDLT) differ; however, there is no report assessing the relationship between graft function and the development of new-onset diabetes mellitus after transplantation (NODAT). We conducted this study to identify the predictive risk factors for NODAT, including graft function after LDLT. Methods The subjects of this study were 175 adult recipients who underwent LDLT at Kyoto University Hospital between 2006 and 2010, and survived for more than 3 months (median observation period, 1046 days). Results The 1-, 2-, and 3-year incidences of NODAT after LDLT were 26.1, 32.0, and 33.4%, respectively. Pre-transplant diabetes was associated with poor survival ( p = 0.0048), whereas NODAT was not associated with patient survival. In the multivariate analysis, recipient age ≥40, a tacrolimus trough level ≥8 ng/mL 3 months after LDLT, and cholinesterase (ChE) <185 IU/L 3 months after LDLT were the independent risk factors for NODAT. Conclusions Poor graft synthetic function 3 months after LDLT as well as older age of the recipient and a higher tacrolimus concentration were strongly associated with NODAT development after LDLT.